Application of Bacillus species for controlling root-knot nematode Meloidogyne incognita in eggplant - El-Nagdi, Wafaa M. A. (2021)
The results of experiment I revealed that Bacillus sp. + B. subtilis significantly reduced the second-stage juvenile (J2) in soil and galls and egg masses in roots, while Bacillus sp. + B. pumilus significantly reduced J2 in roots. Bacillus spp. in pairs were more effective against M. incognita. In experiment II, Bacillus sp. (40 ml) significantly reduced the J2 in soil and galls and egg masses in roots, while B. pumilus (40 ml) significantly reduced the J2 in roots. The nematicidal activity of Bacillus spp. was increased by increasing the applied dose. In experiment III, B. subtilis, when applied three times, significantly reduced the J2 in soil and the J2 and galls in roots, while B. pumilus (applied three times) significantly reduced the egg masses in roots. All Bacillus spp. treatments highly increased the tested growth parameters compared to the controls.